If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-8u + 4) + -3u = 7(u + -3) + -1 Reorder the terms: -2(4 + -8u) + -3u = 7(u + -3) + -1 (4 * -2 + -8u * -2) + -3u = 7(u + -3) + -1 (-8 + 16u) + -3u = 7(u + -3) + -1 Combine like terms: 16u + -3u = 13u -8 + 13u = 7(u + -3) + -1 Reorder the terms: -8 + 13u = 7(-3 + u) + -1 -8 + 13u = (-3 * 7 + u * 7) + -1 -8 + 13u = (-21 + 7u) + -1 Reorder the terms: -8 + 13u = -21 + -1 + 7u Combine like terms: -21 + -1 = -22 -8 + 13u = -22 + 7u Solving -8 + 13u = -22 + 7u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-7u' to each side of the equation. -8 + 13u + -7u = -22 + 7u + -7u Combine like terms: 13u + -7u = 6u -8 + 6u = -22 + 7u + -7u Combine like terms: 7u + -7u = 0 -8 + 6u = -22 + 0 -8 + 6u = -22 Add '8' to each side of the equation. -8 + 8 + 6u = -22 + 8 Combine like terms: -8 + 8 = 0 0 + 6u = -22 + 8 6u = -22 + 8 Combine like terms: -22 + 8 = -14 6u = -14 Divide each side by '6'. u = -2.333333333 Simplifying u = -2.333333333
| x+v^2=w | | 78+12x=620 | | 3x-4/x-5-x-7/2x-10 | | 8=5k-7 | | 5u-7=-8(u+9) | | -83=2x+3x-18 | | (2x^3/y)^3x1/6x^3 | | 28=-y+233 | | 120/12=5X | | 23=-8u-7+2u | | 5(x+8)+2x=-23 | | 2(w+4)=-3(4w-2)+2w | | .03(45x-450)=50 | | 48=x+7x | | x+100=5 | | 5(v-4)+3v=4 | | 0.03(4-x)-0.05(x+2)=0.82 | | -3u+1=-8(u+3) | | -8+54X=27 | | -7(v-5)=2v+8 | | 5x-x=16 | | 130+8x=1042 | | 3h-8=h+4 | | -21=3(y-3)+3y | | 5x+6=16x-3x+54 | | p+11.363=32.663 | | -20=3(w+5)+4w | | 5u+3u=40 | | 6+17v=-15+14v | | 5v+9=17v-4v+81 | | a+7ab-18b^2=0 | | 64x^5y^6=0 |